2020
DOI: 10.3846/btp.2020.12018
|View full text |Cite
|
Sign up to set email alerts
|

Do Investors Experience Heuristics in Earnings Forecasting?

Abstract: This research aims to examine empirically the overreliance on representativeness heuristic and anchoring-adjustment influences experienced by investors in forecasting future earnings. This research was a laboratory experiment with a design of 2x2 full factorial between subject. The results showed that representativeness heuristics were only experienced by investors who obtained positive information. Besides, this study also shows that investors do not overreliance on anchoring-adjustment heuristics. Generally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Dengan kata lain, investor lebih memilih untuk berinvestasi pada perusahaan yang diperkirakan dapat menghasilkan capital gain dibandingkan dengan capital loss. Meski demikian, seluruh tipe informasi yang tersedia di pasar modal memiliki peran penting dalam mempengaruhi transaksi investor dalam menentukan keputusan investasinya (Praditha et. al, 2020).…”
Section: Pendahuluanunclassified
“…Dengan kata lain, investor lebih memilih untuk berinvestasi pada perusahaan yang diperkirakan dapat menghasilkan capital gain dibandingkan dengan capital loss. Meski demikian, seluruh tipe informasi yang tersedia di pasar modal memiliki peran penting dalam mempengaruhi transaksi investor dalam menentukan keputusan investasinya (Praditha et. al, 2020).…”
Section: Pendahuluanunclassified
“…Demonstrating the effect of historical data, Kaustia et al (2008) showed that the prediction of future stock returns is influenced by anchors in the form of historic stock returns in students and, to a lesser degree, in financial market professionals. Praditha, Haliah, Habbe, and Rura (2020) also showed that investors' future earnings forecasts can be affected by various reference values such as past and current earnings, internal company information, and external economic factors. From historic data, Ansar et al, (2014) showed that in large dams building projects, cost plannings are heavily anchored on the similar projects, ignoring the unique environmental and economic situation of each construction site.…”
Section: Predictionmentioning
confidence: 99%
“…A considerable amount of literature has been published on financial behavior (Njegovanović, 2018(Njegovanović, , 2020Gavurova et al, 2019;Hadbaa, 2019;Dewi et al, 2020;Hartanto et al, 2020;Bukalska, 2020). A number of cross-sectional studies suggest that various cognitive limitations and psychological bias change household decision-making in general (Bacik et al, 2020;Jordão et al, 2020;Minasyan et al, 2020), and particularly on consumption/savings (Mody et al, 2012;Ceritoğlu, 2013;Mastrogiacomo & Alessie, 2014;Nguyen et al, 2019;Praditha et al, 2020) and debt/savings (Nofsinger, 2012;Kośny & Piotrowska, 2013;Kłopocka, 2017) ratios in boom-busts periods. However, the study by Zwerenz (2018) also finds that the behavior of real estate prices also significantly influences the cost of capital.…”
Section: Literature Reviewmentioning
confidence: 99%